Argumentasi Saksi Ahli dalam Sidang Penistaan Agama oleh Basuki Tjahaja Purnama di Kepulauan Seribu - Subuki, Makyun; Erowati, Rosida; Sulaiman, Agus (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2023)
Ahok's controversial statements on the Thousand Islands seem not only led to massive and repeated demonstrations, but also linguistic debates in the courtroom. This study aims to examine the arguments of linguists who give statements in the courtroom in response to Ahok's statement. As a qualitative study using discourse analysis as a method of analysis, this study uses a critical argumentation approach developed by Walton (2002 and 2006) to examine how the argument was constructed and evaluate the quality of the argument. The analysis in this study indicates that the opinion of linguists presented by public prosecutors is often inconsistent and not based on adequate linguistic evidence, not only inconsistent with other expert statements, but also with his own statement as a scientist. Conversely, the linguist presented by Ahok's counsel is more consistent and more able to present linguistic evidence more adequately.